2018
DOI: 10.1103/physrevb.98.064420
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of dipolar-coupled XY moments on disordered square lattices

Abstract: The effects of dilution disorder and random-displacement disorder are analyzed for dipolar-coupled magnetic moments confined in a plane, which were originally placed on the square lattice. In order to distinguish the different phases, new order parameters are derived and parallel tempering Monte Carlo simulations are performed for a truncated dipolar Hamiltonian to obtain the phase diagrams for both types of disorder. We find that both dilution disorder and random-displacement disorder give similar phase diagr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…13,23 Structural disorder in imperfect square lattice may similarly lead to spin frustration and the nucleation of vortices. 26 The original motivation to study spin frustrated XY dipolar systems traces back to FeCl 3graphite intercalated compounds with strong dipolar and weak exchange interaction between layered Fe 3+ ions arranged in a honeycomb lattice. 13 Despite successful correlation between experimental and numerical integral properties, a direct visualization of the predicted magnetization configurations in XY dipolar systems, providing an unambiguous proof, is still lacking three decades later.…”
mentioning
confidence: 99%
“…13,23 Structural disorder in imperfect square lattice may similarly lead to spin frustration and the nucleation of vortices. 26 The original motivation to study spin frustrated XY dipolar systems traces back to FeCl 3graphite intercalated compounds with strong dipolar and weak exchange interaction between layered Fe 3+ ions arranged in a honeycomb lattice. 13 Despite successful correlation between experimental and numerical integral properties, a direct visualization of the predicted magnetization configurations in XY dipolar systems, providing an unambiguous proof, is still lacking three decades later.…”
mentioning
confidence: 99%
“…For more exotic lattices, it was found that the low-energy states adopted by an extended system could not be predicted by only considering the relative energies of the building blocks consisting of a few nanomagnets 18,105 . Going beyond Ising-like systems, dipolar XY systems with arrays of coupled discs exhibit complex ordering phenomena 19,20,22 , and the phase diagrams of such XY systems can be modified by structural disorder to give new phases that favour local flux closure 20 . Both the lattice and the moment degrees of freedom define the ordering behaviour.…”
Section: Thermodynamics and Kineticsmentioning
confidence: 99%
“…In addition to using elongated magnets for Ising-like systems, it is possible use circular nanomagnets to create so-called dipolar-coupled XY systems with stripeordered low-energy states 19,22 . Introducing positional disorder in such artificial spin systems modifies the phase diagram to give a microvortex phase 20 . Introducing random interactions and/or removing crystalline order can be a route to obtain spin-glass behaviour 140 , which has been investigated in dipolar XY systems with positional disorder 20 and systems of randomly placed elongated magnets 141 .…”
Section: Box 2 | the Family Of Artificial Spin Systems Beyond Artificmentioning
confidence: 99%
See 2 more Smart Citations